DNA reusability and optoelectronic characteristics of streptavidin-conjugated DNA crystals on a quartz substrate1. Issue 49 (30th May 2015) - Gnapareddy, Bramaramba; Ha, Taewoo; Dugasani, Sreekantha Reddy; Kim, Jang Ah; Kim, Byeonghoon; Kim, Taesung; Kim, Jae Hoon; Park, Sung Ha
<x xml:space="preserve">Abstract</x> We introduced reusability process to fabricate the DNA crystals and studied the optical band gap of them.